PROJECT BASED LEARNING THROUGH PERFORMANCE ORIENTED TASK: ENHANCING EFL LEARNERS’ ORAL COMMUNICATION COMPETENCE - Susiani, Rini; Elyza, Ferlya; Khumaira, Khumaira; Giatama, Ricko Rizki (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
Communication skills are critical in multiple aspects of life. However, many students experience difficulties developing their speaking ability. Therefore, Project Based Learning (PjBL) through showtime project work, plays a vital role in improving students' speaking skills. This study investigated the effect of PjBL through showtime project work on enhancing EFL learners' speaking skills. A quantitative approach with a true experimental design, employing tests and questionnaires as data collection instruments. Seventy students in a senior high school in Banda Aceh were involved as participants, each consisting of 35 students in experimental and control classes. The data were analyzed using inferential statistical analysis. The average posttest score showed a significance level (Sig 2-tailed) of 0.000, which is less than 0.05. Therefore, the alternative hypothesis was accepted. The research result indicated that the students who were taught using PjBL through showtime project work showed improvement in their speaking abilities. The questionnaire findings indicated that over 80% of respondents expressed favorable perceptions regarding the implementation of Project-Based Learning (PjBL) through Showtime Project Work. This method not only enhances language proficiency but also develops critical thinking, facilitates creative expression, and strengthens collaborative competencies among learners.